2023
DOI: 10.3390/nano13111713
|View full text |Cite
|
Sign up to set email alerts
|

Radiolysis-Assisted Direct Growth of Gold-Based Electrocatalysts for Glycerol Oxidation

Abstract: The electrocatalytic oxidation of glycerol by metal electrocatalysts is an effective method of low-energy-input hydrogen production in membrane reactors in alkaline conditions. The aim of the present study is to examine the proof of concept for the gamma-radiolysis-assisted direct growth of monometallic gold and bimetallic gold–silver nanostructured particles. We revised the gamma radiolysis procedure to generate free-standing Au and Au-Ag nano- and micro-structured particles onto a gas diffusion electrode by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…The electrocatalytic oxidation of glycerol by metal electrocatalysts is an effective method for low-energy input hydrogen production in membrane reactors in alkaline conditions. Au-based nanoparticles (Au and Au-Ag NP) were directly synthesized on (and in) carbon paper fibers for application in glycerol electro-oxidation [121]. Co-and Ni-based particles supported on carbon were synthesized by gamma irradiation and used to fabricate electrodes for full cells.…”
Section: Electrocatalysismentioning
confidence: 99%
“…The electrocatalytic oxidation of glycerol by metal electrocatalysts is an effective method for low-energy input hydrogen production in membrane reactors in alkaline conditions. Au-based nanoparticles (Au and Au-Ag NP) were directly synthesized on (and in) carbon paper fibers for application in glycerol electro-oxidation [121]. Co-and Ni-based particles supported on carbon were synthesized by gamma irradiation and used to fabricate electrodes for full cells.…”
Section: Electrocatalysismentioning
confidence: 99%
“…11 Glycerol is easily oxidized into important intermediates for the pharmaceutical and chemical industries, such as glyceraldehyde, glyceric acid, or formic acid, which is a green pathway for dispersal of glycerol. [12][13][14] In addition, it is reported that glycerol can be added into alkaline media to assist in reducing the OER overpotential, at the same time the glycerol is oxidized to some useful chemical intermediates, which results in a "one stone two birds" effect. [15][16][17] Therefore, it is a dominant trend that OER is replaced by the glycerol oxidation reaction (GOR) for water splitting.…”
Section: Introductionmentioning
confidence: 99%